The impact of source languages on the stressing of loanwords in English - Pierre Fournier (Lexis: Journal in English Lexicology)
This study suggests that the parameters accounting for the stressing of loanwords in English should be distinguished from those governing the rest of the English lexicon. This dictionary-based analysis shows that the stress characteristics of source languages are determining factors in the stressing of words of foreign origin in English. Throughout history, the massive influx of words from source languages stressed on the penultimate syllable might have led to a default stress pattern in English being used as a phonological marker to indicate the foreign origin of items. Even though stress preservation is the main parameter accounting for the stress patterns of English loanwords, there is evidence of an ongoing conflict in English between the preservation of the original stress pattern derived from source languages and the application of the default stress pattern instead.